Analysis of A Long Span Structure Considering Prestressed Beams Using ETABS - Jain, Siddharth; Sathbhaiya, Rahul (International Journal of Scientific Research in Civil Engineering, 2020)
A significant number of the unpredictable practices of strengthened concrete cement under shear and flexure are yet to be recognized to utilize this material profitably and financially. The advancement in the understanding and quantitative appraisal of the conduct of part exposed to flexure and shear has been less fantastic. The key idea of shear and inclining pressure quality isn't yet obviously comprehended. Along these lines, further fundamental examination ought to be experienced to decide the component, which brings about shear disappointment of strengthened solid individuals. The investigation presents the investigation of the conduct of strengthened cement deepbeam under seismic ( vibration) stacking and the impact of shear fortification. The impact of variety of web fortification dispersing (both vertical and level) on the shear quality of profound R.C. bar is examined. The overall pattern in split example, the heap diversion attributes and the method of disappointment of profound R.C. shaft under two-focuses stacking are additionally explored. Through the examination, it is seen that under two-focuses stacking framework, inclining splits are normally the primary breaks to be seen free range of the profound bar. In this examination we will contrast profound pillar and PT shaft in G+10 structure utilizing investigation instrument ETABS.
Keywords: PT Beam; Bending Moment; Deflection; Shear Strength; Base Shear; Story Drift